Corneal epithelial cell viability of an ex vivo porcine eye model. (20th January 2014) - Chan, Ka Yin; Cho, Pauline; Boost, Maureen
<x xml:space="preserve">Abstract</x> Purpose The aim was to assess the consistency of corneal epithelial cell viability of an ex vivo porcine eye model. Method Six porcine eye models (four test and two control) were prepared for each experiment. The model has a computer‐controlled mechanical arm, which could move the eyelid of the porcine eye and apply phosphate buffered saline to simulate blinking and lacrimation. The four test eyes were set up to simulate evaporative dry eyes with simulated lacrimation and blinking (one blink and one drop of buffered saline per minute) over three hours. Control A models were set up to collect pre‐experimental baseline data, while those of control B were the same as the test eyes but without lacrimation and blinking simulation. All porcine eyes were kept in a closed chamber with temperature and humidity well controlled. After three hours, the cells of all eyes (except control A, which were assessed immediately before commencement of the experiment) were assessed. The eyes were first dipped into 0.4 per cent trypan blue solution. Following the dissection and separation of the cells, the number of dead cells were then counted under the microscope with a field size of 0.25 mm2. The experiment was repeated 11 times. Results No significant differences were found in the number of dead cells among the four test eyes in both the central and peripheral cornea. There were significantly more dead cells in the test eyes compared to control A but significantly less when compared to control B. More dead cells were found in the central cornea than the peripheral cornea in the test eyes but the difference was not observed in controls A and B. Conclusion Epithelial cell viabilities among the four porcine eye models with simulated lacrimation and blinking were consistent. The majority of cells were viable before the experiment and simulated lacrimation and blinking maintained more viable cells over time.